MONITORING RECYCLED WATER INJECTION INTO A CONFINED AQUIFER IN SINDOS (THESSALONIKI) USING ELECTRICAL RESISTIVITY TOMOGRAPHY (ERT): INSTALLATION AND PRELIMINARY RESULTS - Tsourlos, P.; Vargemezis, G.; Voudouris, C.; Spachos, T.; Stampolidis, A. (Bulletin of the Geological Society of Greece, 2007)
This work describes the installation and preliminary measurements of an electrical resistivity tomography (ERT) system to monitor the injection of recycled water into a confined aquifer in the area of Sindos. The aim is to provide, through time-lapse electrical resistivity tomography (ERT) measurements and processing, geoelectrical images of rather increased volumetric sampling around and between the holes and to obtain improved understanding of the flow and transport of the injected water. The details about the general setting and the design of the injection utility are presented and the construction and installation of the ERT cables into the boreholes are explained in full. Preliminary measurements involving single-hole ERT measurements were obtained and processed with a 2D inversion algorithm to produce images of the subsurface. Results depict a very good correlation between ERT images and the lithology logs an indication of the reliability of the approach. This images offer increased resolution and spatial coverage compared to traditional approaches. The entire ERT permanent installation is of low cost, easy to implement and can be used to understand and evaluate the effects of the water injection process.